Heinrich Heine : writing the revolution - Prochnik, George (Yale University Press, 2020)
A thematically rich, provocative, and lyrical study of one of Germany's most important, world-famous, and imaginative writers.
Keywords: Heine, Heinrich, -- 1797-1856.; Heine, Heinrich, -- 1797-1856 -- Criticism and interpretation.; Heine, Heinrich, -- 1797-1856; Authors, German -- 19th century -- Biography.; Écrivains allemands -- 19e siècle -- Biographies.; BIOGRAPHY & AUTOBIOGRAPHY -- Literary.; Authors, German; 1800-1899; Biography; Biographies; Criticism, interpretation, etc.; Biographies.